Context and importance of biochar research - Madari, Beata Emoke; Maia, Claudia Maria Branco de Freitas; Novotny, Etelvino Henrique (Pesquisa Agropecuaria Brasileira, 2012)
In the context of global warming, major changes are expected in the worldwide energy matrix in the near future. Biomass, a renewable source, as a raw material for energy production, is fundamental in this process. By definition, biochar is any source of biomass previously heated in the absence or at low concentrations of oxygen with the purpose of application to the soil (Maia et al., 2011). The production of biomass for energy (biofuels) requires, above all, soil resources, in terms of occupied land and soil productivity. There are different ways of producing energy from biomass, and the resulting biochar may vary in its physical and chemical composition depending on the kind of biomass and on the conditions of pyrolysis. The technologies that produce biochar as the main product or byproduct of a pyrolysis process are the only ones, among the available biofuel technologies, that may contribute to the improvement or maintenance of soil properties, and, therefore, to the sustainable production of energy and food.